Ecographic biometry of the ocular globe in working horses (Equus ferus caballus) of the province of Córdoba, Colombia - Buitrago Mejia, Jhonny Alberto (2022)
The B-mode ultrasound technique offers the possibility of performing an ocular biometric evaluation of the horse. In Colombia there are no reports on ocular biometric measurements in horses, so the objective of this article was to report the ultrasound appearance of the normal eye and obtain biometric values that can serve as a basis for ocular evaluation. A descriptive study was conducted in the eyes of 50 working horses from the department of Córdoba. The anterior chamber (AC), lens length (Ll), lens width (Lw), vitreous chamber (VC) and axial globe length (AGL) were measured by ultrasound. The sample consisted mainly of Colombian Creole horses (60%) and Appaloosa (32%), 58% were males, average age of 6.7±4.9 years. The biometric values obtained corresponded to AC: 0.68±0.08 cm; Ll: 1.11±0.09 cm, Lw: 2.00±0.16 cm; VC: 1.80±0.15 cm, and AGL: 3.91±0.28 cm. Sex differences were observed for Lw and AGL.